Evaluating and improving the tools for predicting discolouration events in potable water supply system - Al-Ithari, Afrah (Curtin University, 2013)
Complaints regarding discoloured water are one of the major concerns facing water utilities. This research critically evaluates relevant tools and seeks a fundamental understanding of the causes of discoloured water, using considerable system data. Hydraulicevents, as opposed to pipe dirtiness, are critical, raising the question of the relevance of expensive cleaning procedures by water utilities. In order to resolve these issues, a more effective management approach is proposed, sufficient to prevent future discolouration events.